Population genetic and structure of phytophthora spp. causing late blight on potato and tree tomato in central and southern Colombia (2017)
The aim of this study was to describe the frequency of late blight disease in tree tomato crops and to characterize the Phytophthora isolates obtained from tree tomato and potato crops in the central region of Colombia (Antioquia and Cundinamarca States). We evaluated the genetic differentiation between Phytophthora isolates obtained from tree tomato and potato crops. Results from SSR markers showed a significant population structure between populations of Phytophthora isolated from potato and tree tomato crops. We showed that isolates of Phytophthora spp. are predominantly of the Al matmg type. Results also suggest that the population genetic structure of Phytophthora can be shaped by the genetic variation across species (P. infestans and P. betacei) and the geographic origin of the isolate (central or southern region)